PENGARUH KEPEMIMPINAN TRANSFORMASIONALTERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL DALAM RANGKA MENGHADAPI PERSAINGAN MENYONGSONG AEC PADA 2015 (Studi pada Guru Di SMANegeri di Kec. Mranggen Kab. Demak) (Proceeding Fakultas Ekonomi, 2014)
The purpose of this research was to examine the influence of transformational leadershipon organizational citizenship behavior (OCB) mediated by job satisfaction and organizational commitment on the teachers of State Senior High School in Mranggen District, Demak Regency. OCB is an individual's behavior needed in order to face the AEC in 2015 that will be a very tight competition in quality human resources. The research was a census study because the respondents are all teachers in SMAN Mranggen District, Demak Regency, totally 95. Data obtained from questionnaires consist of 4 variables and 65 indicators with 7 likert scale.Data processing for statistical tests performed with SPSS version 19. The results indicate that transformational leadership has positif and significant influence on job satisfaction, job satisfaction has positif dan significant influence on organizational citizenship behavior, transformational leadership has no influence on organizational citizenship behavior, transformational leadership has positif and significant influence on organizational commitment, organizational commitment has positif and significant influence on organizational citizenship behavior, job satisfaction has a positive and significant influence to organizational commitment, job satisfaction mediates the effect of transformational leadership on organizational citizenship behavior, organizational commitment mediates the influence of transformational leadership on organizational citizenship behavior, organizational commitment does not mediate the effect of job satisfaction on organizational citizenship behavior and job satisfaction does not mediate the effect of transformational leadership on commitment organizational. Keywords: Transformational leadership, job satisfaction, organizational commitment, organizational citizenship behavior